KOMPARASI MODEL JIGSAW DENGAN TWO STAY TWO STRAY TERHADAP HASIL BELAJAR - Muhammad Doni; Hanesman Hanesman (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This study aims to determine the differences in the Jigsaw type cooperative learning model with the Two Stay Two Stray type on the learning outcomes of the XI Grade Automatic Control System Expertise in the Engineering and Air Conditioning Technique Program at SMK Negeri 3 Pariaman. This type of research is an experiment in the form of Time Series Design that is used in class XI TPTU A with two learning models namely, Jigsaw model and Two Stay Two Stray model. The results showed the average value of the Jigsaw model was 81.67 and the average value of the Two Stay Two Stray model was 76.46. Obtained t test results with significance 0.05 which obtained tcount> t table (3,568> 2,013) which means that Ho is rejected and Ha is accepted. Then it can be concluded that there is a difference between the Jigsaw type cooperative learning model with the Two Stay Two Stray type on the learning outcomes of the XI Grade Automatic Control System Expertise in the Engineering and Air Conditioning Technique Program at SMK Negeri 3 Pariaman. Keywords: Comparison, Jigsaw, Two Stay Two Stray, Learning Outcomes